PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII-3 SMP NEGERI 29 MEDAN TAHUN PEMBELAJARAN 2019/2020 - Rosita Rosita (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
The population in this study were all grade VII-3 students of SMP Negeri 29 Medan for the Academic Year 2019/2020 which consisted of 2 classes and each class consisted of 30 people. Data collection techniques: 1) Give a test question (pretest) to students. 2) Check and score each item at the same time. 3) Provide treatment with a contextual teaching and learning model to different classes. 4) Give test questions (posttest) to students. 5) Tabulate the scores given. The results of hypothesis testing, namely the average difference test or t test, obtained the price of tcount = 2.19 with ttable = 1.984 for n1 = 30, n2 = 30, dk = 58.